Proposal of Stroop test cut‐off values as screening for neuropsychological impairments in cirrhosis: A Japanese multicenter study. Issue 6 (18th March 2021) - Kondo, Yasuteru; Iwasa, Motoh; Kawaratani, Hideto; Miyaaki, Hisamitsu; Hanai, Tatsunori; Kon, Kazuyoshi; Hirano, Hirotaka; Shimizu, Masahito; Yoshiji, Hitoshi; Okita, Kiwamu; Koike, Kazuhiko
Abstract: Aim: Despite its relevant clinical impact and high prevalence, covert hepatic encephalopathy (HE) still remains underdiagnosed. As patients with liver cirrhosis tend to be older in Japan, more suitable tests for the elderly and cut‐off values based on this attribute are needed. Recently, a Stroop test has been developed and validated for the screening and diagnosis of covert HE in the United States. The present study aims to establish the cut‐off values of the Stroop test to screen covert HE. Methods: This study was a prospective multicenter cross‐sectional endeavor. We undertook a survey of 311 cirrhotic patients, administering the number connection test (NCT)‐A and ‐B and the Stroop‐off and ‐on test. Results: We determined the cut‐off values of Stroop test results for cirrhotic patients in a variety of age ranges. The cut‐off value of the Stroop test was strongly correlated with age. There was a significant correlation between the results of NCT‐B and age, and Stroop‐on test results showed a correlation with serum albumin (Alb) levels. Serum Alb ≤3.2 g/dl could have the potential to be an objective biomarker of covert HE. In addition, stepwise logistic regression analysis revealed a relationship between the results of the Stroop‐on test and plasma ammonia levels. Conclusions: We established the cut‐off values of Stroop test results and confirmed the efficacy of the Stroop test as a simple tool for assessing cognitive alterations. The Stroop test could be suitable as a necessary minimum for the diagnosis of covert HE.